SCIENTIFIC ATTITUDE AND CRITICAL THINKING SKILLS IN SECONDARY SCHOOL STUDENTS: THE IMPACT OF GENDER AND MANAGEMENT - Babu , Murathoti Rajendra Nath; Atokali; Lahon , Ankita; Padmanaban , Srinivasan (Bangladesh Journal of Multidisciplinary Scientific Research, 2025)
Students’ future academic achievement in secondary school depends on developing both a scientific mindset and critical thinking abilities. The study aimed to measure the level of scientific attitude and critical thinking skills among secondary school students and to identify any significant differences in their scientific attitude and critical thinking skills based on gender and management style. A descriptive survey research design was employed to conduct the study. A sample of 200 Class IX students was randomly selected from government and private schools in the Kohima and Dimapur districts of Nagaland. Two research instruments were used for data collection: the scientific attitude questionnaire developed by the investigators and the Critical Thinking Skills Scale developed by Murthy (2014), which was modified to suit the needs and context of Nagaland. The collected data were analyzed using percentages, means, standard deviations, correlations, chi-square tests, and t-tests for independent samples. The study revealed that the level of scientific attitude and critical thinking skills among secondary school students varied. Scientific attitude and critical thinking skills were not significantly influenced by gender. Scientific attitude and critical thinking skills were significantly influenced by management. It was found that there is a positive correlation between scientific attitude and critical thinking skills among secondary school students. The findings of this study suggest that teachers should design an engaging science curriculum that incorporates more hands-on activities, project-based learning, classroom discussions, model exhibitions, science fairs, science museums, and field trips in order to foster a scientific mindset in their pupils. JEL Classification Codes: I21, I24, J16.